Prednisone-hydrogen sulfide releasing hybrid shows improved therapeutic profile in asthma - Cerqua, Ida; Granato, Elisabetta; Corvino, Angela; Severino, Beatrice; D’Avino, Danilo; Simonelli, Martina; Perissutti, Elisa; Scognamiglio, Antonia; Mirra, Davida; D’Agostino, Bruno; Caliendo, Giuseppe; Rossi, Antonietta; et al. (Frontiers in Pharmacology, 2023)
Hydrogen sulfide (H2S) is emerging as an important potential therapeutic option for respiratory inflammatory diseases. In this study, we investigated the effectiveness of a novel corticosteroid derivative, that is chemically linked to an H2S donor, in managing asthma features. The effects of prednisone (PS), H2S donor (4-hydroxybenzamide; TBZ), and their combination (PS-TBZ) have been evaluated in vitro and in vivo. The in vitro experiments were conducted using lipopolysaccharidestimulated J774 macrophages, while the in vivo experiments utilizing an experimental asthma model. In the in vitro study we found that PS-TBZ exhibited an increased effect compared to the individual parent compounds in modulating the production of inflammatory mediators. TBZ also significantly reduced bronchial contractility and enhanced bronchial relaxation. In the in vivo experiments, where we administered PS, TBZ, or PS-TBZ to ovalbumin-sensitized BALB/c mice, we confirmed that PS-TBZ had a significantly better action in controlling airway hyperreactivity as compared to TBZ or PS alone. Moreover, PS-TBZ was more effective in restoring salbutamol-induced relaxation. The immunohistochemistry analysis demonstrated a significant reduction in the production of α-SMA and procollagen III, indicating the efficacy of PS-TBZ in controlling airway remodeling. Moreover, PS-TBZ also promoted epithelial repair, recovery of the bronchial and parenchyma structure and inhibited mucin production. In conclusion, PS-TBZ offers an important opportunity to optimize the beneficial impact of corticosteroids on asthma features.